DEMENTIA EXPERT LINK TO IMPROVE VETERANS EXPERIENCE WITH RURAL CAREGIVING (DELIVER). (11th November 2018) - Freytes, I; Schmitzberger, M; Findley, K; Griffiths, P; Kunik, M; Rupper, R; Pettey, K
Abstract: While the VA has a plethora of evidence-based caregiving support programs, many with tele-health components, these programs remain "siloed"- available only to caregivers who live where the program is offered. To help increase access to services, this quality improvement project, DELIVER Caregiving funded by the VA's Office of Rural Health developed an innovative infrastructure to: a) assess the needs of rural Veterans living with dementia and their caregivers and b) facilitate access to existing resources and tele-health programs that are personalized, proactive, Veteran-centric, accessible from home and, aligned with individualized needs and preferences. First, we are testing the viability of conducting a comprehensive telephone-based needs assessment using the Benjamin Rose Institute Care Consultation (BRI-C) Platform, to triage Veteran/caregiver dyads to programs that best meet their needs. DELIVER care consultants will guide caregivers in identifying issues they would like to address, help the develop a step-by-step action plan to address their needs, and build ongoing relationship focused on prevention and monitoring caregivers to support them as they work toward their goals. If the BRI-C is found to be viable, we will validate the platform's ability to target and match Veterans and caregivers' needs and preferences via a comprehensive needs assessment and referral infrastructure. We hypothesis that the DELIVER program will have an impact on caregivers' burden, depression, self-efficacy and Veterans' healthcare utilization and quality of life.